PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA-BIOLOGI PADA SISWA UPT SPF SMP NEGERI 38 MAKASSAR PULAU KODINGARENG - Rosmiati, Etty; Seprida, Riski; Ariaty, Eka (Jurnal Biogenerasi, 2024)
The objectives of this research are (1) to determine the increase in student activity. (2) Knowing the learning outcomes of Biology Science students through the application of jigsaw type cooperative learning to increase the activities and learning outcomes of Biology Science for UPT SPF students at SMP Negeri 38 Makassar Kodingareng Island, especially class VIII B, totaling 30 people. The data collection technique in this research is in the form of tests at the end of each cycle and student activities or activeness as well as analysis of test results. The research results showed that in the first cycle, student attendance was 69.99%, student learning activity reached 50.47% with high criteria, the average student learning outcome was 67.4, with classical learning completeness 56.67%. Meanwhile in cycle II attendance was 81.67%, student learning activity reached 77.62% with very high criteria, average student learning outcomes were 81.66%, with classical learning completeness at 100%. This shows an increase in both activities and student learning outcomes from cycle I and cycle II.